UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN MATEMATIKA MELALUI METODE PROBLEM SOLVING PADA SISWA KELAS II SDN 12 LEMBAH MELINTANG - warni warni (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on the results of student learning II SDN Class 12 Valley Crossing in Mathematics sub Perform Operation Count Campuranditemukan that results for students in the subjects of Mathematics sub Perform Operation Count mixture is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about the efforts to improve student learning outcomes in mathematics sub Perform Operation Count lalui Problem Solving Methods in the Class II SDN 12 Valley Crossing West Pasaman.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subject of the study consisted of 27 students of Class II SDN 12 Valley Crossing. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the method of problem solving can improve student learning outcomes in mathematics sub Perform Operation Count mixture at SDN 12 Valley Crossing. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 57.11 (Enough) increased to 83.33 (good) with an increase of 26.22%.